Remix multilingualism Hip-Hop, ethnography and performing marginalized voice - Williams, Quentin (Bloomsbury Academic, 2017)
Remixing multilingualism" is conceptualised in this book as engaging in the linguistic act of using, combining and manipulating multilingual forms. It is about creating new ways of 'doing' multilingualism through cultural acts and identities and involving a process that invokes bricolage. This book is an ethnographic study of multilingual remixing achieved by highly multilingual participants in the local Hip Hop culture of Cape Town. In globalised societies today previously marginalized speakers are carving out new and innovating spaces to put on display their voices and identities through the creative use of multilingualism. This book contributes to the development of new conceptual insights and theoretical developments on multilingualism in the global South by applying the notions of stylization, performance, performativity, entextualisation and enregisterment. This takes place through interviews, performance analysis and interactional analysis, showing how young multilingual speakers' stage different personae, styles, registers and language varieties
Keywords: Gesellschaft; Mehrsprachigkeit; Hip-Hop; Ethnolinguistik; Marginalität; Subkultur; Südafrika (Staat); Kapstadt; Multilingualism / Social aspects; Multilingualism / South Africa; Performing arts / Social aspects; Sociolinguistics; Multilingualism; South Africa